An Analysis Phatic Expression on Hotel Transylvania Animated Movie - Tiara Putri Safira; Sofwan Arif Agil; Pratiwi Amelia (Proceedings Series on Social Sciences & Humanities, 2024)
In contemporary filmmaking, the portrayal of emotions is pivotal, with phatic communication playing a crucial role. Phatic communication, involving verbal interactions aimed at maintaining social relationships rather than conveying information, enhances narrative and character development. This study examines phatic expressions in the animated film "Hotel Transylvania," directed by Genndy Tartakovsky, to uncover the deeper meanings and social significance of these seemingly simple interactions. The analysis reveals that greetings, casual conversations, and social courtesies in the film not only establish and maintain social bonds but also contributing to the film’s charm and authenticity. By exploring phatic communication in "Hotel Transylvania," this research offers insights into sociolinguistics and communication studies, emphasizing the importance of these expressions in storytelling and the functions of phatic expression in social context so that the readers can apply it to enhance their conversations.